Complete Resection of a Torcular Herophili Hemangiopericytoma without Sinus Reconstruction: A Case Report and Review of the Literature - Salah-Edine Safi; Julie Godfrain; Herbert Rooijakkers; Frederic Collignon (Case Reports in Surgery)
A 78-year-old woman presented to the emergency department with mild headaches and a sudden onset of blurred vision. Computerized tomography scan and magnetic resonance imaging showed what was described at first as a meningioma invading and occluding the torcular Herophili, the posterior third of the superior sagittal sinus and the proximal part of the right transverse sinus. Gross total resection of the tumor was performed without reconstructing dural sinuses. The patient was discharged home without new neurological deficit. Histopathology was in favor of a hemangiopericytoma Grade II World Health Organization (WHO). Total body positron emission tomography [18F]fluorodeoxyglucose found no secondary location. Radiotherapy was planned post-operatively.